Poverty Alleviation Model in Tasikmalaya City: An Analytic Network Process Approach - Apip Supriadi; GUSTI TIA ANDRIANI; ASO SUKARSO; JUMRI (Jurnal Ekonomi Kuantitatif Terapan, 2026)
Poverty alleviation requires a sustainable multidimensional strategy encompassing empowerment, welfare, and investment. This study applies the Analytic Network Process (ANP) to evaluate poverty reduction strategies in Tasikmalaya City, Indonesia. Data were collected through pairwise comparisons from experts and analyzed using the SuperDecisions software. The results indicate that Entrepreneurship Empowerment is the top priority (34.7%), followed by Social Security (29.0%), Regional Investment (24.8%), and Provision of Basic Needs (11.5%). Sensitivity analysis confirms the consistency of results, where empowerment remains dominant under various parameter scenarios. The novelty of this study lies in integrating empowerment and welfare strategies with contextual sub-criteria in a city-level ANP model. These findings support Sustainable Development Goal (SDG 1) and emphasize empowerment as the foundation for sustainable poverty alleviation in Indonesia. Keywords: poverty alleviation, analytic network process, empowerment, social protection, Indonesia, SDGs JEL Classification: I32, O21, R58